PENGGUNAAN METODE PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BELAJAR MANDIRI MAHASISWA JURUSAN PENDIDIKAN AKUNTANSI PADA MATA KULIAH AKUNTANSI PERPAJAKAN - Wafrohtur rohmah; Suyatmini Suyatmini (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2013)
The aim of the research is to improve Accounting Education Department’s student self learning forTax Accounting lesson by using problem based learning method. The subject of this classroomaction research involved students of III a class Accounting Education Department in 2011/2012academic year, who studies Tax accounting (36 students). Flow method design research from Kemmisand Taggart by cycle model. Data collection used by observation technique, analysis procedure byusing interactive analysis model from Milles Huberman. Based on the research result in reflectionevaluation,can be concluded that: 1) by using the constructive procedure of problem based learningmethod the self learning of Accounting Education Department’s student for Tax Accounting lessonincreased; 2) the function of teacher as facilitator, motivator, and learning source not as dictator oflearning; 3) class situation become more active-creative; 4) student can be active in learning, able todo scheduled learning, have a high self confident, be critical in learning and have self enforcement.This method will be more effective to improve students self learning if they are explained about problembased learning, case study task can be solved in class, and reflection-evaluation in the end of sessionmust be provided by the teacher.